Do Liquidation Values Affect Financial Contracts? Evidence from Commercial Loan Contracts and Zoning Regulation* - Benmelech, Efraim; Garmaise, Mark J.; Moskowitz, Tobias J. (Quarterly Journal of Economics, 2005)
We examine the impact of asset liquidation value on debt contracting using a unique set of commercial property non-recourse loan contracts.We employ commercial zoning regulation to capture the flexibility of a property's permitted uses as a measure of an asset's redeployability or value in its next best use.Within a census tract, more redeployable assets receive larger loans with longer maturities and durations, lower interest rates, and fewer creditors, controlling for the current value of the property, its type, and neighborhood.These results are consistent with incomplete contracting and transaction cost theories of liquidation value and financial structure.